Incorporation of database approach into contractual issues: Methodology and practical guide for organizations - Chong, Heap Yih; Phuah, T. (Elsevier BV, 2013)
A total avoidance of project disputes is an impossible situation. Yet, the purpose should identify the perspectives of minimizing disputes or maximizing avoidance. By referring to past experiences on the causes and the suggested solutions, this research reckons that it can assist in avoiding or resolving similar situations at the onset of the dispute occurrence. Therefore, the objectives are: (a) to propose and develop a practical database system that can be employed by organizations to manage the past experiences, particularly for contractual issues, and (b) to validate and evaluate the database system from related organizations. Two actual projects were referred prior to finalizing the database system's structure. Microsoft Office Access tool was selected due to its wide-spread availability and user-friendliness to construction related organizations. The database system was evaluated and received positive feedback. It renders an insight toward the effort in avoidance of project disputes through the database approach.